Trajetórias de vida e mudança de identidade sexual: quando não se encontra o pote de ouro no final do arco-íris - Silva, Odacyr Roberth Moura da (2017)
This master thesis aims to know life trajectories of individuals who who claimed to have changed their sexual identity from homosexual to heterosexual. Specifically, it was analyzed triggering factors and consequences of the discovery and abandonment of homosexuality, as well as to understand the diversity of experiences related to family, social and religious life in the life trajectory of these subjects. This is an exploratory, qualitative, cross-sectional study, which had the participation of four males, over 18 years old, who declared that they had changed their sexual identity. The sampling process was intentional and delimited from internal diversification and empirical saturation criteria. Participants were located through snowball technique. The instrument was based on a narrative interview and a semi-structured interview script. For data analysis, the phenomenological method was used for psychological investigation, which revealed six units of meaning: Context for the "production" of homosexuality; Situations of prejudice; Affective/sexual experiences; Discovery and experience of homosexuality; Context of sexual reorientation; Uncomfortable with the term ex-gay; Changes in other aspects of life. Prejudice was the phenomenon found on the basis of main transformations that occurred, although it was not always admitted or interpreted as something negative by participants. They pointed to dissatisfaction with gay lifestyle as the main driver of the change of sexual identity. There was a strong internalization of religious representations about homosexuality, understood by them as a deviation from natural and healthy sexuality. The internalization of these representations provided the creation of a negative social identity for these individuals as homosexuals. The transition from homosexual to heterosexual status meant for them a better social valuation, greater self-acceptance, as well as potentializing the possibility of developing a full and happy life according to heteronormative model, which they believe to be the only legitimate and true way to live the sexuality.